Edukasi Pembayaran dan Pencatatan Keuangan Digital bagi Usaha Pop Ice Pekanbaru - Andariyani, Ira Meike; Wahab, Wirdayani; Martha, Dewi; Gusnafitri, Gusnafitri (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the national economy, but still face challenges in financial management, especially in micro businesses such as Pop Ice sellers in school environments. Unstructured manual recording often makes it difficult for business actors to monitor cash flow. This Community Service (PKM) activity aims to increase payment literacy and digital financial recording for Pop Ice business actors in Pekanbaru. Through a participatory approach, activities begin with needs analysis, training through workshops, demonstrations and direct mentoring. Partners are trained to use financial applications that are easy to operate to record daily transactions and manage digital payments such as QRIS. The results of the activity show an increase in partners' ability to record transactions accurately, prepare simple reports, and understand the financial condition of their business, thereby supporting business sustainability and competitiveness.